Ultrahigh oil-resistant low-smoke halogen-free material for offshore oil platform and preparation method of ultrahigh oil-resistant low-smoke halogen-free material

By using silane cross-linking grafting method and acid polycondensation reaction in materials for offshore petroleum platforms, combined with the use of sorbitol, an island-type cross-linking structure is formed, which solves the problem of poor oil resistance of existing materials, achieves ultra-high oil resistance and stability, and meets the NEK606 standard.

CN119684708APending Publication Date: 2025-03-25SHANGHAI WANMA POLYMER MATERIALS RESEARCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411880765.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing materials for offshore oil platforms have poor oil resistance and are difficult to meet the actual requirements in harsh environments such as high temperature, high humidity, and high electrolytes.

Method used

The traditional silane cross-linking grafting method and the new acid alcohol polycondensation cross-linking method are adopted, and the grafting reaction is carried out at a certain temperature by matrix resin and modified resin, and sorbitol is added to the acid alcohol reaction to form a uniform island cross-linking structure, which improves the overall cross-linking degree and oil resistance of the material.

Benefits of technology

It realizes the ultra-high oil resistance of the material, and the change rate can be controlled below 5%, meeting the requirements of the NEK606 standard, and improving the overall performance and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198146550000061
    Figure BDA0005198146550000061
  • Figure BDA0005198146550000071
    Figure BDA0005198146550000071
Patent Text Reader

Abstract

The invention provides an ultrahigh oil-resistant low-smoke halogen-free material for an offshore oil platform and a preparation method of the ultrahigh oil-resistant low-smoke halogen-free material, the ultrahigh oil-resistant low-smoke halogen-free material comprises matrix resin, modified resin, a flame retardant, a compound curing agent, mineral oil, an initiator, a cross-linking agent and an antioxidant, and the compound curing agent is a composition of epoxy resin, methyl tetrahydrophthalic anhydride and sorbitol. According to the invention, matrix resin and modified resin are subjected to a grafting reaction at a certain temperature by using a silane cross-linking grafting method, anhydride, epoxy resin and sorbitol are subjected to a reaction under a certain condition by using a cross-linking mode of an acid-alcohol polycondensation reaction, and a uniform sea-island cross-linked structure is formed in the material; a small amount of water is generated in the polycondensation reaction process, and a large amount of water vapor can generate pre-crosslinking in the product, so that a certain proportion of sorbitol is added, the water vapor generated by polycondensation is slowly and uniformly dispersed in the product, and the generated water vapor can further promote crosslinking of the silane grafted material, so that the overall crosslinking of the material is more thorough; and the oil resistance is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cables, and relates to a halogen-free material for an offshore oil platform and its preparation, and in particular to an ultra-high oil-resistant, low-smoke halogen-free material for an offshore oil platform and its preparation method. Background Art

[0002] Offshore oil platforms are offshore structures mainly used for drilling wells. Offshore oil platforms are equipped with equipment including drilling, power, communication, navigation, and safety and life-saving facilities. Offshore oil platforms use cables as the nervous system connecting these facilities, which plays an indispensable role. As cables for electrical equipment used in special industries, cables for offshore oil platforms must be able to meet the working conditions and safety requirements of offshore oil platforms from the aspects of safety, reliability, and environmental adaptability. Compared with ordinary cables, their particularity is also highlighted.

[0003] At present, most materials used in offshore oil platforms adopt radiation cross-linking and silane cross-linking methods to improve the performance of the materials. However, after irradiation, the oil resistance change rate of the material can only reach 10%-15%. In more harsh environments such as high temperature, high humidity, and high electrolytes, the above oil resistance data is difficult to meet actual requirements. For this reason, the market needs materials with high oil resistance. Summary of the invention

[0004] In order to solve the defect of poor oil resistance of existing materials for offshore oil platforms, the present invention provides an ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms and a preparation method thereof. The present invention utilizes a traditional silane cross-linking grafting method to make a base resin and a modified resin undergo a grafting reaction at a certain temperature, and then adopts a novel acid-alcohol polycondensation reaction cross-linking method to make anhydride, epoxy resin and sorbitol react under certain conditions to form a uniform sea-island cross-linking structure inside the material. A small amount of water is generated during the polycondensation reaction. Because a large amount of water vapor will cause pre-crosslinking in the product, a certain proportion of sorbitol is added in the acid-alcohol reaction to make the water vapor generated by the polycondensation slowly and evenly dispersed in the product, and the generated water vapor will further promote the cross-linking of the silane grafted material, so that the overall cross-linking of the material is more thorough and the oil resistance is better.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention first provides an ultra-high oil-resistant low-smoke halogen-free material for an offshore oil platform. The ultra-high oil-resistant low-smoke halogen-free material for an offshore oil platform comprises, by weight: 100 parts of a base resin, 30-60 parts of a modified resin, 150-200 parts of a flame retardant, 3-6 parts of a compound curing agent, 15-35 parts of a mineral oil, 1-3 parts of an initiator, 1-5 parts of a cross-linking agent and 2-4 parts of an antioxidant. The compound curing agent is a composition of an epoxy resin, methyltetrahydrophthalic anhydride and sorbitol.

[0007] In the present invention, acid anhydride and epoxy resin are used as main cross-linking agents to form a cross-linking network through polycondensation reaction. However, polycondensation reaction is a stepwise polymerization reaction and produces a small amount of water.

[0008] If the generated water vapor cannot effectively escape from the reaction system, bubbles will form inside the material or cause pre-crosslinking, which will affect the final performance and structure of the material and lead to material inhomogeneity or performance degradation.

[0009] The present invention adds a certain proportion of sorbitol, which is hydrophilic and can absorb and disperse the water vapor generated during the polycondensation process, which helps to prevent the water vapor from accumulating locally inside the material, so that the generated water vapor is slowly and evenly dispersed in the material, thereby reducing the risk of pre-crosslinking. The generated water vapor will further promote the crosslinking of the silane grafted material, promote the formation of a uniform island-type crosslinking structure inside, so that the overall crosslinking of the material is more thorough, the oil resistance is better, and it is helpful to improve the overall performance and stability of the material.

[0010] As a preferred embodiment of the present invention, the matrix resin is compounded from ethylene vinyl acetate copolymer and polypropylene, and the mass ratio of ethylene vinyl acetate copolymer to polypropylene is 60-80:20-40.

[0011] As a preferred embodiment of the present invention, the VA content of ethylene vinyl acetate copolymer is 14%-26%, and the melt index is 1-20 g / 10 min; the polypropylene is homopolymer polypropylene, and the melt index is 2-5 g / 10 min.

[0012] As a preferred embodiment of the present invention, the modified resin is obtained by compounding EPDM rubber and styrene-ethylene-butylene-styrene block copolymer in a ratio of 10:5-10.

[0013] As a preferred embodiment of the present invention, the flame retardant includes one or a mixture of magnesium hydroxide, aluminum hydroxide and zinc borate.

[0014] As a preferred embodiment of the present invention, in the composite curing agent, the mass ratio of epoxy resin, methyltetrahydrophthalic anhydride and sorbitol is 2:1-2:0.5, wherein the epoxy resin is bisphenol A type epoxy resin with an epoxy value of 0.30-0.47eq / 100g.

[0015] As a preferred embodiment of the present invention, the kinematic viscosity of the mineral oil is 80-200 mm 2 / S.

[0016] As a preferred embodiment of the present invention, the initiator comprises one or a mixture of dicumyl peroxide, benzoyl peroxide and imidazole.

[0017] As a preferred embodiment of the present invention, the crosslinking agent includes one or a mixture of vinyltrimethoxysilane and vinyltriethoxysilane; the antioxidant includes one or a mixture of antioxidant 1010, antioxidant 1076 and antioxidant 168.

[0018] The present invention also provides a method for preparing an ultra-high oil-resistant, low-smoke, and halogen-free material for an offshore oil platform, the preparation method comprising the following steps:

[0019] 1) weighing the base resin, modified resin, flame retardant, initiator and crosslinking agent according to the above formula, adding them into a twin-screw extruder, and setting the extruder temperature at 160°C, 170°C, 180°C, 190°C, and 200°C; granulating in a single screw, and setting the granulation temperature at 150°C, 145°C, 140°C, 130°C, and 125°C to obtain a grafted masterbatch;

[0020] 2) Weigh the compound curing agent, mineral oil and antioxidant according to the above formula, add them into the reaction kettle and mix them at a mixing temperature of 180°C for 60-90 minutes. The viscosity of the mixed liquid is between 100-250 mm 2 / S, the reaction is stopped to obtain a catalytic liquid auxiliary agent;

[0021] 3) The grafted masterbatch obtained in step 1) and the catalytic liquid auxiliary agent obtained in step 2) are extruded in a single screw at an extrusion temperature of 170°C, 180°C, 195°C, 200°C, and 190°C. After the materials are extruded, they are cured in an oven at 60°C-80°C for 24 hours to obtain an ultra-high oil-resistant, low-smoke, and halogen-free material for offshore oil platforms; wherein the mass ratio of the grafted masterbatch to the catalytic liquid auxiliary agent is 85-90:10-15.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) The present invention utilizes the traditional silane cross-linking grafting method to make the base resin and the modified resin undergo a grafting reaction at a certain temperature, and then adopts a new acid-alcohol polycondensation reaction cross-linking method to make the acid anhydride, epoxy resin and sorbitol react under certain conditions to form a uniform sea-island cross-linking structure inside the material. A small amount of water will be generated during the polycondensation reaction. Because a large amount of water vapor will cause pre-crosslinking in the product, a certain proportion of sorbitol is added in the acid-alcohol reaction to make the water vapor generated by the polycondensation slowly and evenly dispersed in the product, and the generated water vapor will further promote the cross-linking of the silane grafted material, so that the overall cross-linking of the material is more thorough and the oil resistance is better.

[0024] 2) The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms of the present invention meets the requirements of the NEK606 standard.

[0025] 3) The ultra-high oil-resistant, low-smoke, and halogen-free material prepared by the present invention is suitable for cables used in offshore oil platforms. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] The present invention first provides an ultra-high oil-resistant low-smoke halogen-free material for an offshore oil platform. The ultra-high oil-resistant low-smoke halogen-free material for an offshore oil platform comprises, by weight: 100 parts of a base resin, 30-60 parts of a modified resin, 150-200 parts of a flame retardant, 3-6 parts of a compound curing agent, 15-35 parts of a mineral oil, 1-3 parts of an initiator, 1-5 parts of a cross-linking agent and 2-4 parts of an antioxidant. The compound curing agent is a composition of an epoxy resin, methyltetrahydrophthalic anhydride and sorbitol.

[0028] Preferably, the matrix resin is a compound of ethylene vinyl acetate copolymer and polypropylene, and the mass ratio of ethylene vinyl acetate copolymer to polypropylene is 60-80:20-40.

[0029] Preferably, the VA content of ethylene vinyl acetate copolymer is 14%-26%, and the melt index is 1-20 g / 10 min; the polypropylene is homopolymer polypropylene, and the melt index is 2-5 g / 10 min.

[0030] Preferably, the modified resin is obtained by compounding EPDM rubber and styrene-ethylene-butylene-styrene block copolymer in a ratio of 10:5-10.

[0031] Preferably, the flame retardant includes one or a mixture of magnesium hydroxide, aluminum hydroxide and zinc borate.

[0032] Preferably, in the composite curing agent, the mass ratio of epoxy resin, methyltetrahydrophthalic anhydride and sorbitol is 2:1-2:0.5, wherein the epoxy resin is bisphenol A type epoxy resin with an epoxy value of 0.30-0.47eq / 100g.

[0033] Preferably, the kinematic viscosity of the mineral oil is 80-200 mm 2 / S, the present invention adopts white oil.

[0034] Preferably, the initiator comprises one or a mixture of dicumyl peroxide, benzoyl peroxide and imidazole.

[0035] Preferably, the crosslinking agent includes one or a mixture of vinyltrimethoxysilane and vinyltriethoxysilane.

[0036] Preferably, the antioxidant includes one or a mixture of antioxidant 1010, antioxidant 1076, and antioxidant 168.

[0037] In the present invention, the raw materials used in Examples 1 to 3 are: ethylene vinyl acetate copolymer, manufactured by Formosa Plastics, brand 7470K; polypropylene, manufactured by Daqing Petrochemical, brand T30S; ethylene propylene diene monomer rubber, manufactured by Mitsui Sinopec, brand 3112PM; styrene-ethylene-butylene-styrene block copolymer, manufactured by Baling Petrochemical, brand 503T; magnesium hydroxide, manufactured by Albemarle, brand H5IV; aluminum hydroxide, manufactured by Albemarle, brand 104LEO; epoxy resin, manufactured by Baling Petrochemical, brand E44; methyltetrahydrophthalic anhydride, manufactured by Qingyang Chemical, brand SHY-9602; white oil, manufactured by Zhengxin Petroleum Technology, brand T320; diisopropylbenzene peroxide, manufactured by Nouryon; imidazole, manufactured by Daiso Chemical; vinyl trimethoxysilane, manufactured by Hubei New Blue Sky; antioxidant 1010, manufactured by BASF; antioxidant 1076, manufactured by BASF.

[0038] The raw materials used in the comparative example are: EVA resin, manufactured by Yihuaping, brand HM500; polyethylene resin, manufactured by Mitsui, brand SP0540; compatibilizer, manufactured by Nengzhiguang, brand MC329; aluminum hydroxide, manufactured by Zhongchao, brand 01DH; magnesium hydroxide, manufactured by Aifel, brand S12; coupling agent, manufactured by Dow Corning, brand 11-100; cross-linking agent, manufactured by Nouryon, brand DCP; antioxidant, manufactured by Double Bond Chemical, brand 1035; lubricant, manufactured by British Croda, brand EBS.

[0039] Example 1

[0040] The present embodiment provides an ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms, which is prepared from the following raw materials: 80 parts of ethylene-vinyl acetate copolymer, 20 parts of polypropylene, 30 parts of ethylene propylene diene rubber, 30 parts of styrene-ethylene-butylene-styrene block copolymer, 100 parts of magnesium hydroxide, 100 parts of aluminum hydroxide, 3 parts of epoxy resin, 3 parts of methyltetrahydrophthalic anhydride, 0.75 parts of sorbitol, 25 parts of white oil, 0.5 parts of diisopropyl peroxide, 0.5 parts of imidazole, 5 parts of vinyltrimethoxysilane, 1 part of antioxidant 1010 and 1 part of antioxidant 1076.

[0041] The preparation method is:

[0042] 1) The above-mentioned base resin, modified resin, flame retardant, initiator and cross-linking agent are added to a twin-screw extruder in proportion, and the extruder is set at 160°C, 170°C, 180°C, 190°C, and 200°C; then granulation is carried out in a single screw, and the granulation setting temperature is 150°C, 145°C, 140°C, 130°C, and 125°C to obtain a grafted masterbatch.

[0043] 2) Add the above-mentioned composite curing agent, white oil and antioxidant into the reaction kettle in proportion and mix them at a mixing temperature of 180°C for 60-90 minutes. The viscosity of the mixed liquid is between 100-250 mm 2 / S, the reaction is stopped to obtain a catalytic liquid auxiliary agent.

[0044] 3) The grafted masterbatch in step 1) and the catalytic liquid auxiliary agent in step 2) are extruded in a single screw according to the ratio of (85-90): (15-10), and the extrusion temperature is 170°C, 180°C, 195°C, 200°C, 190°C. After the material is extruded, it is placed in a 60°C-80°C oven for 24 hours for curing to obtain an ultra-high oil-resistant, low-smoke, and halogen-free material for offshore oil platforms. The cured material can meet the requirements of the NEK606 standard, and the oil resistance performance required by the standard can be controlled at a change rate of less than 5%.

[0045] Example 2

[0046] The present embodiment provides an ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms, which is prepared from the following raw materials: 60 parts of ethylene vinyl acetate copolymer Formosa Plastics brand 7470K, 40 parts of polypropylene, 20 parts of ethylene propylene diene rubber, 10 parts of styrene-ethylene-butylene-styrene block copolymer, 100 parts of magnesium hydroxide, 50 parts of zinc borate, 2 parts of epoxy resin, 1 part of methyltetrahydrophthalic anhydride, 0.5 parts of sorbitol, 15 parts of white oil, 2 parts of benzoyl peroxide, 1 part of diisopropyl peroxide, 1 part of vinyl triethoxy silane, 3 parts of antioxidant 1010 and 1 part of antioxidant 168.

[0047] The preparation method is:

[0048] 1) The above-mentioned base resin, modified resin, flame retardant, initiator and cross-linking agent are added to a twin-screw extruder in proportion, and the extruder is set at 160°C, 170°C, 180°C, 190°C, and 200°C; then granulation is carried out in a single screw, and the granulation setting temperature is 150°C, 145°C, 140°C, 130°C, and 125°C to obtain a grafted masterbatch.

[0049] 2) Add the above-mentioned composite curing agent, white oil and antioxidant into the reaction kettle in proportion and mix them at a mixing temperature of 180°C for 60-90 minutes. The viscosity of the mixed liquid is between 100-250 mm 2 / S, the reaction is stopped to obtain a catalytic liquid auxiliary agent.

[0050] 3) The grafted masterbatch in step 1) and the catalytic liquid auxiliary agent in step 2) are extruded in a single screw according to the ratio of (85-90): (15-10), and the extrusion temperature is 170°C, 180°C, 195°C, 200°C, 190°C. After the material is extruded, it is placed in a 60°C-80°C oven for 24 hours for curing to obtain an ultra-high oil-resistant, low-smoke, and halogen-free material for offshore oil platforms. The cured material can meet the requirements of the NEK606 standard, and the oil resistance performance required by the standard can be controlled at a change rate of less than 5%.

[0051] Example 3

[0052] The present embodiment provides an ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms, which is prepared from the following raw materials: 70 parts of ethylene vinyl acetate copolymer, 30 parts of polypropylene, 20 parts of ethylene propylene diene rubber, 20 parts of styrene-ethylene-butylene-styrene block copolymer; 170 parts of aluminum hydroxide, 2 parts of epoxy resin, 2 parts of methyltetrahydrophthalic anhydride, 0.5 parts of sorbitol, 25 parts of white oil, 1 part of imidazole, 2 parts of vinyl triethoxy silane and 3 parts of antioxidant 1076.

[0053] The preparation method is:

[0054] 1) The above-mentioned base resin, modified resin, flame retardant, initiator and cross-linking agent are added to a twin-screw extruder in proportion, and the extruder is set at 160°C, 170°C, 180°C, 190°C, and 200°C; then granulation is carried out in a single screw, and the granulation setting temperature is 150°C, 145°C, 140°C, 130°C, and 125°C to obtain a grafted masterbatch.

[0055] 2) Add the above-mentioned composite curing agent, white oil and antioxidant into the reaction kettle in proportion and mix them at a mixing temperature of 180°C for 60-90 minutes. The viscosity of the mixed liquid is between 100-250 mm 2 / S, the reaction is stopped to obtain a catalytic liquid auxiliary agent.

[0056] 3) The grafted masterbatch in step 1) and the catalytic liquid auxiliary agent in step 2) are extruded in a single screw according to the ratio of (85-90): (15-10), and the extrusion temperature is 170°C, 180°C, 195°C, 200°C, 190°C. After the material is extruded, it is placed in a 60°C-80°C oven for 24 hours for curing to obtain an ultra-high oil-resistant, low-smoke, and halogen-free material for offshore oil platforms. The cured material can meet the requirements of the NEK606 standard, and the oil resistance performance required by the standard can be controlled at a change rate of less than 5%.

[0057] Comparative Example 1

[0058] This comparative example is a radiation cross-linked oil-resistant, low-smoke, halogen-free material that meets the NEK606 standard; the specific formula is as follows: 100 parts of polyolefin resin, including 70 parts of EVA resin; 30 parts of polyethylene resin; 5 parts of compatibilizer, halogen-free flame retardant including 50 parts of aluminum hydroxide and 100 parts of magnesium hydroxide, 1.5 parts of coupling agent, 2 parts of cross-linking agent, 1 part of antioxidant and 1 part of lubricant.

[0059] The materials obtained in Examples 1 to 3 and the material obtained in Comparative Example 1 were tested. The testing methods refer to the relevant provisions in Table 1 of ENKTS-60-2016. The test results are shown in Table 1.

[0060] Table 1. Test results

[0061]

[0062]

[0063] It can be seen from Table 1 that the oil resistance of the material of the present invention is significantly better than that of existing products on the market, and other properties can meet the relevant requirements of the NEK606 standard.

[0064] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. An ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms, characterized in that: The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms comprises, by weight: 100 parts of base resin, 30-60 parts of modified resin, 150-200 parts of flame retardant, 3-6 parts of compound curing agent, 15-35 parts of mineral oil, 1-3 parts of initiator, 1-5 parts of cross-linking agent and 2-4 parts of antioxidant, wherein the compound curing agent is a composition of epoxy resin, methyltetrahydrophthalic anhydride and sorbitol.

2. The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms according to claim 1, characterized in that: The matrix resin is obtained by compounding ethylene vinyl acetate copolymer and polypropylene, and the mass ratio of ethylene vinyl acetate copolymer to polypropylene is 60-80:20-40.

3. The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms according to claim 2, characterized in that: The VA content of ethylene vinyl acetate copolymer is 14%-26%, and the melt index is 1-20g / 10min; the polypropylene is homopolymer polypropylene, and the melt index is 2-5g / 10min.

4. The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms according to claim 1, characterized in that: The modified resin is obtained by compounding EPDM rubber and styrene-ethylene-butylene-styrene block copolymer in a ratio of 10:5-10.

5. The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms according to claim 1, characterized in that: The flame retardant comprises one or a mixture of magnesium hydroxide, aluminum hydroxide and zinc borate.

6. The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms according to claim 1, characterized in that: In the composite curing agent, the mass ratio of epoxy resin, methyltetrahydrophthalic anhydride and sorbitol is 2:1-2:0.5, wherein the epoxy resin is bisphenol A type epoxy resin with an epoxy value of 0.30-0.47eq / 100g.

7. The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms according to claim 1, characterized in that: The kinematic viscosity of the mineral oil is 80-200 mm 2 / S.

8. The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms according to claim 1, characterized in that: The initiator comprises one or a mixture of dicumyl peroxide, benzoyl peroxide and imidazole.

9. The ultra-high oil-resistant, low-smoke, halogen-free material for offshore oil platforms according to claim 1, characterized in that: The crosslinking agent includes one or a mixture of vinyl trimethoxy silane and vinyl triethoxy silane; the antioxidant includes one or a mixture of antioxidant 1010, antioxidant 1076 and antioxidant 168.

10. A method for preparing ultra-high oil-resistant, low-smoke, halogen-free materials for offshore oil platforms, characterized in that: The preparation method comprises the following steps: 1) Weighing a base resin, a modified resin, a flame retardant, an initiator and a crosslinking agent according to the formula of any one of claims 1 to 9, adding them into a twin-screw extruder, and setting the extruder temperature at 160° C., 170° C., 180° C., 190° C., and 200° C.; granulating in a single screw, and setting the granulation temperature at 150° C., 145° C., 140° C., 130° C., and 125° C. to obtain a grafted masterbatch; 2) Weigh the compound curing agent, mineral oil and antioxidant according to any one of claims 1 to 9, add them into a reaction kettle and mix them at a mixing temperature of 180° C. for 60 to 90 minutes. The viscosity of the mixed liquid is between 100 and 250 mm 2 / S, the reaction is stopped to obtain a catalytic liquid auxiliary agent; 3) The grafted masterbatch obtained in step 1) and the catalytic liquid auxiliary agent obtained in step 2) are extruded in a single screw at an extrusion temperature of 170°C, 180°C, 195°C, 200°C, and 190°C. After the materials are extruded, they are cured in an oven at 60°C-80°C for 24 hours to obtain an ultra-high oil-resistant, low-smoke, and halogen-free material for offshore oil platforms; wherein the mass ratio of the grafted masterbatch to the catalytic liquid auxiliary agent is 85-90:10-15.